Investing in low-trust countries: On the role of social trust in the global mutual fund industry - MASSA, Massimo (Institutional Knowledge at Singapore Management University, 2022)
We hypothesize that social trust, in mitigating contracting incompleteness, may have an important effect on the activeness and effectiveness of delegated portfolio management. Using a complete sample of worldwide open-end mutual funds, we find that trust is positively associated with the activeness of funds and that trust-related active share delivers superior performance (e.g., approximately 2% per year for cross-border investments). Moreover, "trust in the market" and "trust in managers" play important yet different roles for different types of cross-border delegated portfolio management. Our results suggest that trust acts as a fundamental building block for delegated portfolio management.